A novel at-home bleaching technique modified by a CPP-ACP paste - Borges, Boniek Castillo Dutra (2011)
This study was designed to evaluate in vitro the efficacy of a novel at-home bleaching technique using 10% or 16% carbamide peroxide modified by casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) and its influence on the microhardness of bleached enamel. A total of 40 bovine incisors were divided into four groups (n=10) according to the bleaching agent used: 10% carbamide peroxide only; a blend of 10% carbamide peroxide and a CPP-ACP paste; 16% carbamide peroxide only; and a blend of 16% carbamide peroxide and a CPP-ACP paste. During the 14-day bleaching regimen, the samples were stored in artificial saliva. The Vickers microhardness and color of the teeth were assessed at baseline (T0) and immediately after the bleaching regimen (T14) using a microhardness tester and a spectrophotometer, respectively. The degree of color change was determined by the Commission Internationale de l'Eclariage (CIE) L*a*b* system (ΔE, ΔL*, Δa*, and Δb*) and Vita shade guide parameters. The data were analyzed by analysis of variance and the Tukey test (p<0.05). The teeth that were bleached with a blend of peroxide (10% or 16%) and the CPP-ACP paste presented increased microhardness values at T14 compared with T0, whereas the samples that were bleached with peroxide only did not show any differences in their microhardness values. All of the bleaching agents were effective at whitening the teeth and did not show a statistically significant difference using the CIEL*a*b* system (ΔE, ΔL*, Δa*, and Δb*) or the Vita shade guide parameters. The use of a CPP-ACP paste with carbamide peroxide bleaching agents increased the bleached enamel's microhardness and did not have an influence on whitening efficacy.